Analisis Pertumbuhan Ikan Nila (Oreochromis niloticus) pada Sistem Budidaya Kolam Beton di Dusun IV Desa Fadoro Lasara Kota Gunungsitoli - Ratna Dewi Zebua; Betzy Victor Telaumbanua; Destriman Laoli; Nistiarni Zebua; Okniel Zebua (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the growth of tilapia (Oreochromis niloticus) cultivated in a concrete pond system in Dusun IV, Fadoro Lasara Village, Gunungsitoli City. The concrete pond system was chosen for its advantages in land efficiency, ease of management, and ability to maintain stable water quality. The research method employed a quantitative experimental approach over 60 days, with 200 Nile tilapia as the study subjects. The parameters observed included absolute weight and length gain, specific growth rate (SGR), feed conversion ratio (FCR), and survival rate (SR). The results showed that the average weight of the fish increased from 5.12 grams to 98.46 grams, with a length increase of 12.5 cm. The SGR was recorded at 4.29% per day, FCR at 1.38, and SR at 96.5%. These results indicate that the concrete pond system can support optimal tilapia growth. This study recommends the application of concrete ponds as an efficient aquaculture alternative, particularly in areas with limited land and resources. This system has proven to be adaptive to local conditions and contributes to increased productivity and income for aquaculture farmers.